La ordinatio y los paratextos en la Crónica troyana de Juan de Burgos - María Sanz Julián (Atalaya)
The Crónica Troyana by Juan de Burgos is the Spanish literature Trojan Matter which enjoyed the longest popularity. Between the first version, printed in Burgos in 1490, and the last one, which appeared in Medina del Campo in 1587, more than a dozen editions were published. The Crónica used two Castilian sources, which no longer exist today: a translation of the Historia destructionis Troiae by Guido de la Columna, and a text that is related to the preserved versions of the Sumas de Historia Troyana by Leomarte. In this article we will analyze the ordinatio of the Crónica printed in 1490 and particularly the fragments in the paratexts which, as they do not come directly from the sources mentioned, were probably introduced by the compilator.